Pengaruh Profitabilitas dan Pertumbuhan Penjualan terhadap Struktur Modal pada Perusahaan Pertambangan yang terdaftar di Bursa Efek Indonesia - Yanti, Siti Hajar; Nurfadillah, Mursidah; Fauziah, Fenty (ITB AAS INDONESIA, 2024)
This research was conducted with the aim of determining the effect of Profitability and Sales Growth on Capital Structure in Mining Companies listed on the Indonesia Stock Exchange. This research covers 41 mining companies listed on the Indonesian stock exchange and which have published consecutive annual financial reports from 2020 to 2022. This research uses non-probability sampling techniques. This research uses quantitative methods and research data is analyses using hypothetical statistical techniques with the help of the SPSS 27 for Windows program. The F test results show that profitability and sales growth simultaneously influence capital structure with an R2 value of 26%. The t test results show that the profitability variable affects capital structure, while the sales growth variable does not have a partially significant effect on capital structure.